Spatio-temporal variations of the heat fluxes at the ice-ocean interface in the Bohai Sea - Bin Jia; Libang Xu; Xueen Chen; Wenyan Zhang (Frontiers in Marine Science)
Thermodynamic process between the ice and the ocean plays a critical role in the evolution of sea-ice growth and melting in marginal seas. At the ice-ocean interface, the oceanic heat flux and the conductive heat flux transmitted through the ice layer jointly determine the latent heat flux driving the phase change (i.e., ice freezing/melting). In this study, the determination of two important thermal parameters in the ice module of the HAMSOM ice-ocean coupled model, namely the mixed layer thickness and the heat exchange coefficient at the ice-ocean interface, has been adjusted to improve the model performance. Spatio-temporal variations of heat fluxes at the ice-ocean interface in the Bohai Sea are investigated, based on the validated sea ice simulation in the 2011/2012 ice season. The relationships between the interfacial heat fluxes and oceanic and atmospheric conditioning factors are identified. We found that the surface conductive heat flux through ice shows short-term fluctuations corresponding to the atmospheric conditions, the magnitude of these fluctuations decreases with depth in the ice layer, likely due to reduced influence from atmospheric conditions at greater depths. Atmospheric conditions are the key controlling factors of the conductive heat flux through ice, while the oceanic heat flux is mainly controlled by the oceanic conditions (i.e., mixed layer temperature). Spatially, the value of the oceanic heat flux is larger in the marginal ice zone with relatively thin ice than in the inner ice zone with relatively thick ice. In the Bohai Sea, when ice is growing, heat within the ice layer is transferred upward from the ice base, and the heat is losing at the ice-ocean interface. This heat loss in the inner ice zone is obviously greater than that in the marginal ice zone. Whereas when ice is melting, the opposite is true.